PERKEMBANGAN KESENIAN TRADISIONAL AJENG TAHUN 2010 – 2020 DI SANGGAR SINAR PUSAKA KARAWANG - Suhendy, Suhendy (Jurnal Penelitian Musik, 2022)
Ajeng is one of the traditional arts of Indonesia which is precisely located in Karawang regency, West Java province. Basically the function of Ajeng art as music to welcome guests - large guests. Ajeng is an art that is classified as old and feared extinct, therefore the purpose of this research is to know the development of Ajeng art from 2010 - 2020 and it is expected that Ajeng art can be better known and still show its existence. This research uses descriptive qualitative method, data collection in this research by interview, observation, documentation and theoretical analysis. The object of his research is one of Ajeng's surviving art groups, sanggar Sinar Pusaka Abah Tarim Karawang. The results of this study showed that Ajeng experienced developments, one of which in terms of performance examples: in the past Ajeng only presented instrumentalia music but over time added vocal elements to increase public interest in Ajeng art.